Pulmonary Abnormalities and Carotid Atherosclerosis in Ex-Smokers without Airflow Limitation. (1st February 2015) - Pike, Damien; Kirby, Miranda; Lindenmaier, Tamas J.; Sheikh, Khadija; Neron, Casey E.; Hackam, Daniel G.; Spence, J. David; Fenster, Aaron; Paterson, Nigel A. M.; Sin, Don D.; Coxson, Harvey O.; McCormack, David G.; et al.
Abstract: It is well-established that COPD patients have a burden of vascular disease that cannot be fully-explained by smoking history but the mechanistic links between atherosclerosis and pulmonary disease in COPD patients are not well-understood. Moreover, in ex-smokers without symptoms or other evidence of COPD, subclinical pulmonary and vascular disease, although potentially present, has not been described or evaluated. Hence our aim was to use sensitive three-dimensional (3D) pulmonary and carotid imaging to quantify pulmonary airway/parenchyma abnormalities and atherosclerosis in ex-smokers without airflow limitation or symptoms consistent with COPD. We evaluated 61 subjects without airflow limitation including 34 never- (72 ± 6 years) and 27 ex-smokers (73 ± 9 years), who provided written informed consent to spirometry, plethysmography, 3 He magnetic resonance imaging (MRI) and carotid ultrasound (US) and, for ex-smokers alone, thoracic X-ray computed tomography (CT). Ex-smokers had significantly greater 3 He ventilation defect percent (VDP = 7%, p = 0.001) and carotid total plaque volume (TPV = 250 mm 3, p = 0.002) than never-smokers, although there were no significant differences for spirometry or plethysmography, and CT airway and emphysema measurements were normal. There were univariate relationships for 3 He VDP with carotid intima media thickness (IMT, r = 0.42, p = 0.004), TPV (r = 0.41, p = 0.006) and vessel wall volume (VWV, r = 0.40, p = 0.007). Multivariate models that included age, BMI, FEV1, DLCO and VDP showed that only VDP significantly predicted IMT (β = 0.41, p = 0.001), VWV (β = 0.45, p = 0.003) and TPV (β = 0.38, p = 0.005). In summary, there was imaging evidence of mild airways disease and carotid plaque burden that were related and significantly greater in ex-smokers without airflow limitation than in never-smokers.